On shaggy ridge - Bradley, Phillip (Oxford University Press, 2004)
This study details the dramatic but little-known story of the 1943-44 Ramu Valley campaign in New Guinea that culminated in the battle for Shaggy Ridge. Drawing on the vivid recollections of over 140 veterans and the author's own journeys in the region, the book brings to life Japan's dogged defense of this razorback ridge and how they resisted the Autralians for over four months